Carbon capture potential and costs in Brazil. (10th September 2016) - Rochedo, Pedro R.R.; Costa, Isabella V.L.; Império, Mariana; Hoffmann, Bettina Susanne; Merschmann, Paulo Roberto de C.; Oliveira, Camilla C.N.; Szklo, Alexandre; Schaeffer, Roberto
Abstract: This article estimates carbon capture potentials and costs of energy and industrial facilities in Brazil. These estimates are important for an emerging economy whose energy- and process-related CO2 emissions are expected to grow over time. The Brazilian case is emblematic due to the prospects for carbon capture in biomass processing facilities, such as ethanol distilleries with nearby petroleum sedimentary basins (enhanced oil recovery – EOR – potential through CO2 injection), and for increasing petroleum production and the potential role for carbon capture in industrial plants. Findings show that capture costs are lower for petroleum platforms and hydrogen generation units in oil refineries or ammonia plants. In platforms, CO2 capture should be performed for economic reasons, regardless of environmental concerns. Capture in ethanol distilleries may also occur at reduced costs and become viable, given the additional revenue associated the use of the captured CO2 for EOR in mature oil fields in the country. For the other evaluated sectors, carbon capture is also available but at costs exceeding 30 US/tCO2 and, in some cases, reaching approximately 100 US/tCO2 . Potentials, on the other hand, can get up to 28 MtCO2 /year captured in the oil and gas sector and 47 MtCO2 /year in the cement sector.